1993
DOI: 10.3109/00207459309000595
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Calcification as a Possible Marker of Hallucinations in Schizophrenia

Abstract: Several studies suggest that disturbances of serotonin (5-HT) functions may be involved in the pathophysiology of hallucinations in schizophrenia. It is now well established that the choroid plexus (CP) is innervated by serotonin (5-HT) neurons, which may regulate its activity, and it is possible that decreased 5-HT functions may facilitate the process of its calcification. It is thus conceivable that calcification of the CP may be associated with hallucinations in schizophrenia. I studied in 18 chronic schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…An increased albumin ratio also can be indicative of a decreased CSF flow rate, a dysfunction with numerous physiological causes (Reiber, 1994; Whedon and Glassey, 2009). For example, CSF flow patterns can be disrupted by degenerative and pathological CNS features such as calcification at the choroid plexus, arachnoid cysts and decreased brain volumes, all of which are conditions that have been previously associated with the pathophysiology of psychoses and schizophrenia (Arango et al, 2012; Kuloglu et al, 2008; Marinescu et al, 2013; Narr et al, 2003; Reiber, 1994; Rimol et al, 2012; Sandyk, 1993; Shiga et al, 2012; Veijola et al, 2014; Whedon and Glassey, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased albumin ratio also can be indicative of a decreased CSF flow rate, a dysfunction with numerous physiological causes (Reiber, 1994; Whedon and Glassey, 2009). For example, CSF flow patterns can be disrupted by degenerative and pathological CNS features such as calcification at the choroid plexus, arachnoid cysts and decreased brain volumes, all of which are conditions that have been previously associated with the pathophysiology of psychoses and schizophrenia (Arango et al, 2012; Kuloglu et al, 2008; Marinescu et al, 2013; Narr et al, 2003; Reiber, 1994; Rimol et al, 2012; Sandyk, 1993; Shiga et al, 2012; Veijola et al, 2014; Whedon and Glassey, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Rudin also suggested that any dysfunction of the choroid plexus might reconcile viral and exogenous peptide hypotheses of disease causation, as infectious agents and exogenous peptides might easily pass across this barrier perhaps in genetically susceptible individuals (Rudin, 1981b). Others report that calcification of the choroid plexus can be associated with symptoms of psychosis and cognitive deficiencies, presenting much like schizophrenia (Marinescu et al, 2013; Sandyk, 1993). The role of arachnoid membrane dysfunction in schizophrenia is also an understudied subject; however, a series of reports link the presence of arachnoid cysts to schizophrenia-like symptoms (Kuloglu et al, 2008; Narr et al, 2003; Shiga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Two general symptom studies have explored the relationship between TD and choroid plexus calcification. The first study did not report significant differences in the severity of positive TD between those with and without calcification of the choroid plexus (Sandyk, 1993a). The second study showed an association between the length of left choroid plexus calcification and the severity of positive TD, though the direction of this correlation was not specified (Bersani et al, 1999a).…”
Section: Gross Cortical Structure and The Ventricular Systemmentioning
confidence: 93%
“…Sandy et al [4] suggest that CPC size positively correlated with intensity of hallucination, and was unrelated to delusions, conceptual disorganization, grandiosity, excitement and global Brief Psychiatric Rating Scale psychopathology score, but might be a major marker for hallucinations seen in schizophrenia. The same study found that CPC was not related to patients' age, sex, age at onset of psychiatric illness, duration of psychiatric illness, duration of patients' education, and present IQ [4,5]. There was a significant relationship between CPC and depressive symptoms seen in patients with schizophrenia, this coincided with a change in the 5-HT functions of CPC.…”
Section: Discussionmentioning
confidence: 99%